EFEKTIVITAS TEKNIK ANESTESI LOW FLOW DIBANDINGKAN TEKNIK ANESTESI INHALASI STANDAR PADA ANAK USIA 1-6 TAHUN YANG MENJALANI OPERASI DI PROF. DR. I.G.N.G. NGOERAH DENPASAR - Kurniyanta, Putu; Suarjaya, Putu Pramana; Narakusuma, Fajar (E-Jurnal Medika Udayana; Vol 12 No 6 (2023): E-Jurnal Medika Udayana, 2023)
Since the discovery of sevoflurane, it has been commonly used due to its many advantages, including its safety profile for pediatric anesthesia practice. However, currently no ideal recommendation for how much gas flow should be used during induction in children. High fresh gas flow (FGF) causes waste of anesthetic and oxygen gases, making it both uneconomical and environmentally polluting. To date, there have been very few studies on low FGF in children, so there is no best and efficient method for reducing the need for large amounts of induction gas. The aim of this study is to determine the effectiveness of the low low anesthesia (LFA) technique in reducing sevoflurane volume, induction time, and hemodynamics during surgery in children undergoing surgery. This is a case-control study conducted at Prof. Dr. I.G.N.G Ngoerah Hospital in Denpasar. Forty-six children aged 1 - 6 years underwent elective surgery and were anesthetized with sevoflurane and randomly divided into two groups: the case group using the low-flow anesthesia technique and the control group using the standard anesthesia technique. The case and control groups were statistically similar in terms of demographic data. However, the volume of sevoflurane used from the time of premedication to intubation was significantly different (p > 0.05) between the two groups (35.5 ml vs 44.5 ml). The induction times were not significantly different (209s vs 201s, p<0.05). Additionally, no significant difference was observed regarding hemodynamic stability during anesthesia. Keywords : anesthesia induction, hemodynamic stability, low flow anesthesia, sevoflurane